Athletic Administrators Report of Emergency Action Plan Adoption in Secondary School Athletics: The Influence of Athletic Training Services - Samantha E. Scarneo-Miller; Lindsay J. DiStefano; Johna K. Register-Mihalik; Rebecca L. Stearns; Craig R. Denegar; Douglas J. Casa (Journal of Applied Sports Management, 2019)
This study describes the emergency action plan (EAP) adoption in secondary school athletics reported by athletic administrators in the United States. Utilizing best-practice criteria, a questionnaire assessed athletic administrators’ knowledge and adoption of an EAP in their athletics program. A majority of athletic administrators reported having an EAP; however, the EAP often lacked the necessary components to be compliant with best-practice guidelines. Further, access to an athletic trainer was associated with increased EAP adoption and adopting a venue specific EAP. Athletic administrators should utilize these data to facilitate improved policy adoption and management of athletics programs.
Keywords: Critical care; emergencies; emergency planning; sports